Sistem Aduan Berasaskan Web untuk Pengurusan Aduan yang Efisien - Osman, Muhamad Hazim; Abdul Jalil, Abdul Hariz Idlan; Lokman, Muhamad Akmal Irfan (Multidisciplinary Applied Research and Innovation, 2023)
The UTHM Residential Complaint System (URCS) was developed with the goal of turning the existing manual complaints system into an online, web-based complaints system. The fellows of residential colleges who will receive complaints from students are the principal users of URCS. With HTML, PHP, SQL, and CSS being used as programming languages, URCS is developed using software like Bracket, phpMyAdmin, and Xampp as the primary database. The administration will be notified of the user complaints through several accounts. As a guide for developing this system, the development of the Agile model is used. UTHM Residential Complaint System (URCS) is available, making management’s handling of complaint data more effective than it already is. The current management methods for residential colleges have drawn the participation of roughly 22 respondents. The vast majority of respondents concur that this system can assist and facilitate the production of complaints by users. Residential college management could benefit from this system. The research on this system will concentrate on the creation of a system with unique features and a user-friendly user interface. Because of this, creating a system that will provide differentiation from other systems will be difficult for us. A variety of interface displays are created, such as staff and higher interfaces that distinguish between management roles, to demonstrate the importance of this system’s point of differentiation. As a result, the goal will be consistent with the primary goal that will provide value to the development of this system